Hubungan Antara Tingkat Stres dan Fatigue dengan Kualitas Tidur pada Pasien Diabetes Melitus - Eki Amelia Vega; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (NAJ Nursing Applied Journal, 2025)
Diabetes mellitus affects various dimensions of health, including sleep pattern disruptions, which can be exacerbated by high levels of stress and prolonged fatigue. This study aims to explore the correlation between stress levels and fatigue with sleep quality in diabetes mellitus patients at Puskesmas Bangetayu Semarang. This research adopts an observational-analytical design with a cross-sectional approach, involving 119 individuals selected through purposive sampling, based on characteristics that meet the study criteria. Data collection was conducted using PSQI, PSS-10, and FAS instruments, which assess sleep quality, stress levels, and fatigue, respectively. Data analysis was carried out using univariate and bivariate approaches, employing the gamma test to determine the degree of association between variables. The findings indicate that 42.9% of respondents experience high levels of stress, 52.9% report severe fatigue, and 60.5% have poor sleep quality. Correlation analysis yielded a p-value of 0.001 (<0.05), with a correlation coefficient of 0.774 for stress and 0.753 for fatigue, confirming a significant relationship between both variables and sleep quality.